Analysis of factors influencing intention to use of bitcoin among business owners and non-business owners in Iloilo City - Balbuena, Christine May; Balino, John Philip; Cabrera, Marie Lou; Dianon, Kyra Ann; Lingga, Gilmarie Joyce
The existence of cryptocurrencies, particularly Bitcoin, has brought changes into the way how business and daily transactions are carried out. There has been an ongoing debate of what Bitcoin really is, from being a digital currency into a speculative investment, which resulted to many people having developed their own definition of what Bitcoin is and how they are going to use or not use it for their own benefit. This study was developed in order to analyze the factors that drive an individual to use or not use Bitcoin through the Modified Theory Acceptance Model (TAM) formulated by the researchers. Data collection on the respondents was determined through mixed methods and data analysis was done through STATA with the use of the Structural Equation model. Results showed that the constructs of Perceived Usefulness, Perveived Risk, and Subjective Norm has a significant impact on business owner's intention to use Bitcoin while Perceived Ease of Use, Perceived Risk, Subjective Norm, and Technological curiosity have a significant effect on non-business owners' intention to use Bitcoin.